Factors Relating Selection Of Traditional Birth Attendant Assistance In Sukakarya Village, Samarang Sub-District, Garut - Wahyudin Wahyudin; Hasbi Taobah Ramdani; Yesi Yuliani (Jurnal Medika Cendikia, 2015)
Maternal and infant mortality rate is the most important part related to the age of life literacy of Indonesian population. Data from Health Department of Garut District shows that childbirth rate by traditional birth attendants (TBAs) in public health center of Sukakarya only 28% in 2012. The purpose of this study was to analyze the relationships between the level of knowledge, economic status, service delivery by traditional birth attendants and the selection of delivery assistance by TBAs. The method was used analytical research with cross sectional design. The participants were pregnant mothers who recorded in the data of maternal deliveries target. The data was collected by interview from 45 pregnant mothers. The results showed that the majority of pregnant mothers (64.0%) had a good perception level of service delivery by TBAs (P= 0.521). The most pregnant mothers (92.9%) who have a poor level of knowledge and low level of socioeconomic (75.9%) chose to deliver by assistance of traditional birth attendants (P = 0.004; P= 0.003, respectively). This study suggested that primary healthcare professionals are expected to increase pregnant mothers’ knowledge in term of selecting birth attendance assistance by promote health education, thus can support them to choose delivery at healthcare professionals.